The effects of multiwalled carbon nanotubes and Bacillus subtilis treatments on the salt tolerance of maize seedlings - Luo, Ying; Zeng, Wenzhi; Lei, Guoqing; Hou, Yaling; Ao, Chang; Chen, Haorui; Gaiser, Thomas; Srivastava, Amit Kumar (Frontiers in Plant Science, 2022)
Nanomaterials, including multiwalled carbon nanotubes (MWCNTs), have been recently applied in agriculture to improve stress resistance, leading to contradictory findings for antioxidant responses and mineral nutrient uptake. A pot experiment involving maize in low-salinity sandy loam soils was conducted with the application of different concentrations (0, 20, 50 mg/L) of MWCNTs and the growth-promoting rhizobacterium Bacillus subtilis (B. subtilis). The dose-dependent effect of MWCNTs was confirmed: 20 mg/L MWCNTs promoted the accumulation of osmolytes in maize, particularly K+ in the leaves and roots, significantly increased the leaf indoleacetic acid content, decreased the leaf abscisic acid content; but the abovementioned promoting effect decreased significantly in 50 mg/L MWCNT-treated plants. We observed a synergistic effect of the combined application of MWCNTs and B. subtilis on plant salt tolerance. The increased lipid peroxidation and antioxidant-like proline, peroxidase (POD), and catalase (CAT) activities suggested that MWCNTs induced oxidative stress in maize growing in low-salinity soils. B. subtilis reduced the oxidative stress caused by MWCNTs, as indicated by a lower content of malondialdehyde (MDA). The MWCNTs significantlyincreased the leaf Na+ content and leaf Na+/K+ ratio; however, when applied in combination with B. subtilis, the leaf Na+/K+ ratio decreased sharply to 69% and 44%, respectively, compared to those of the control (CK) group, the contents of which were partially regulated by abscisic acid and nitrate, according to the results of the structural equation model (SEM). Overall, the increased osmolytes and well-regulated Na+/K+ balance and transport in plants after the combined application of MWCNTs and B. subtilis reveal great potential for their use in combating abiotic stress.